2021
DOI: 10.3389/fsoc.2021.728095
|View full text |Cite
|
Sign up to set email alerts
|

Household Coping Strategies During the COVID-19 Pandemic in Chile

Abstract: Chile was severely hit by the COVID-19 pandemic. The implementation of social distancing measures strongly affected the Chilean economy: the unemployment rate grew rapidly as well as the proportion of population temporarily excluded from the labour force. This article analyses the strategies deployed by Chilean households to cope with the impact of the pandemic at the intersection with household structure and its socio-economics characteristics. Secondary data analysis from the Encuesta Social COVID-19 (COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
3
10
0
4
Order By: Relevance
“…The observed increases in food insecurity in Mexico versus other countries may relate to the lack of policy responses compared to the other countries in this investigation. Social protection programs such as the Coronavirus Supplement in Australia ( 74 ), the Canadian Emergency Response Benefit ( 73 ), the Emergency Family Income program in Chile ( 75 ), Universal Credit in the UK ( 76 ), and the Federal Pandemic Unemployment Compensation program in the US ( 73 ) were altered or implemented, potentially contributing to the declines or lack of change in food insecurity observed between 2019 and 2020. In contrast, limited economic responses to the pandemic in Mexico have been noted, for example, including the provision of loans to small- and medium-sized business and enabling advanced withdrawal of pension funds ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increases in food insecurity in Mexico versus other countries may relate to the lack of policy responses compared to the other countries in this investigation. Social protection programs such as the Coronavirus Supplement in Australia ( 74 ), the Canadian Emergency Response Benefit ( 73 ), the Emergency Family Income program in Chile ( 75 ), Universal Credit in the UK ( 76 ), and the Federal Pandemic Unemployment Compensation program in the US ( 73 ) were altered or implemented, potentially contributing to the declines or lack of change in food insecurity observed between 2019 and 2020. In contrast, limited economic responses to the pandemic in Mexico have been noted, for example, including the provision of loans to small- and medium-sized business and enabling advanced withdrawal of pension funds ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have stressed that IC is protective against critical events during the life course, such as the transition to adulthood (Nauck & Ren, 2018), the loss of a partner in late adulthood (Roan & Raley, 1996), and the increase in support needs in old age (Zhang et al, 2014). In addition, recent studies on the shock of the COVID‐19 pandemic in families have shown the protective effect of IC in terms of economic stability and availability of care (Ayuso et al, 2020; Cantillon et al, 2021; Gilligan et al, 2020; Palma & Araos, 2021). This is particularly important in countries with limited welfare provision, such as Latin American countries, where intergenerational support plays a central role in meeting basic needs.…”
Section: Intergenerational Coresidence Across Countriesmentioning
confidence: 99%
“…Di Chile sebanyak 60,3% rumah tangga mengalami penurunan pendapatan saat pandemi Covid-19 (Palma and Araos, 2021).…”
Section: Bahasanunclassified
“…Berdasarkan survey yang dilakukan oleh SMERU, beberapa coping mechanism yang paling umum dilakukan rumah tangga untuk mencukupi kebutuhan sehari-hari selama pandemi antara lain dengan menjual atau menggadaikan barang, mengurangi pengeluaran non makanan, meminjam uang kepada kerabat, mengurangi pengeluaran makanan, dan mekanisme lainnya (Izzati Al, 2021). Sementara itu di Chile, sebagian besar masyarakat melakukan penghematan pada saat awal terjadi pandemi, dan kemudian sebagai upaya untuk coping mechanism terbanyak adalah dengan berhutang dan dekapitalisasi (Palma and Araos, 2021).…”
Section: Bahasanunclassified